Pengaruh Pertumbuhan Penjualan, Leverage Operasi, dan Profitabilitas terhadap Struktur Keuangan pada Balitbang Provinsi Sumatera Utara - Humairoh Qolbiah Siregar; Juliana Nasution (VISA: Journal of Vision and Ideas, 2023)
The objective of the research was to find out the empirical evidence about the influence of profitability, selling growth, firm size, and structure aktiva on Capital structure in real estate and property companies listed in BEI (Indonesia Stock Exchange). The research used associative research method with quantitative Data. The methods of data collection conducted be literature study. The population Balitbang Provinsi Sumatera Utara companies in the periode of 2011-2015, and 30 of Them were used as the samples with the criteria determined by the research. The Result of the research showed that, simultaneously, the variables of profitability, Selling growth, firm size, and structure aktive had positive and significant Influence on companies capital structure. Partially, the variables of profitability Had negative and insignificant influence on capital structure, selling growth had Negative and insignificant influence on capital structure, firm size had positive and Significant influence on capital structure, and structure aktive had negative but Significant influence on real estate and property companies listed in BEI. Keyword: profitability, selling growth, firm size, structure aktive, capital Structure.